2016
DOI: 10.3892/ol.2016.4138
|View full text |Cite
|
Sign up to set email alerts
|

Novel insight into MALAT-1 in cancer: Therapeutic targets and clinical applications

Abstract: Abstract. Long non-protein-coding RNAs (lncRNAs) are emerging as important gene expression regulators that are linked to various biological processes at the post-transcriptional and transcriptional levels. lncRNAs are known to be important in cell proliferation, cell differentiation, apoptosis and metastasis. Metastasis-associated lung adenocarcinoma transcript 1 (MALAT-1), a novel lncRNA, is highly conserved amongst mammals. In addition, it has been considered to act as an oncogene, depending on the tumor sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 83 publications
(116 reference statements)
0
22
0
1
Order By: Relevance
“…Since its discovery, several studies have reported the link of MALAT-1 to other cancers, including gallbladder-, cervical-, non-small cell lung- (NSCLC), colorectal-, and breast cancer. In most cases, MALAT-1 is upregulated in cancer and is associated with metastasis, cell proliferation, apoptosis, and migration, as well as with clinically unfavorable prognostic parameters [ 16 , 49 , 103 , 104 , 105 , 106 ].…”
Section: Lncrna Candidates In Breast Cancermentioning
confidence: 99%
“…Since its discovery, several studies have reported the link of MALAT-1 to other cancers, including gallbladder-, cervical-, non-small cell lung- (NSCLC), colorectal-, and breast cancer. In most cases, MALAT-1 is upregulated in cancer and is associated with metastasis, cell proliferation, apoptosis, and migration, as well as with clinically unfavorable prognostic parameters [ 16 , 49 , 103 , 104 , 105 , 106 ].…”
Section: Lncrna Candidates In Breast Cancermentioning
confidence: 99%
“…Single cell RNASeq analyses showed high levels of expression of various metastasis-related markers (particularly the MIF/CD44/CD74/CXCR4 signaling axis), as well as LINE-1 retrotransposons. In addition, the MTFs uniformly expressed very high levels of MALAT1, a long non-coding RNA transcript known to be involved in control of metastasis [ 25 , 26 ], as well as additional long non-coding transcripts implicated in cancer progression. When the cultured PDAC MTFs were orthotopically transplanted into the pancreas in mice, they formed well-differentiated islands there.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, the MALAT1 sequence was infused into mice pulmonary carcinoma and the tumor growth and metastasis was inhibited (Gutschner et al, 2013b). Compared to primary tumors, the level of MALAT1 was further elevated in metastatic tumors, suggesting a correlation between the levels of MALAT1 and malignant tumors (Ren et al, 2016).…”
Section: Discussionmentioning
confidence: 99%